1970
DOI: 10.3126/jncs.v22i0.519
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aluminum Corrosion in Chloride and Nitrate Media and its Inhibition by Nitrite

Abstract: Aluminum corrosion has been studied in aqueous chloride and nitrate media. Potentiodynamic method is applied to carry out the individual effect of chloride and nitrate ions on the commercial grade aluminum corrosion. In both chloride and nitrate media the corrosion behavior is affected at pH 4 and 10. The corrosion rate of aluminum increases with the increase of concentrations of chloride and nitrate ions. In both media corrosion behavior is significant at higher pH value due to the instant dissolution of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…These super-Faradaic efficiencies are reported in the literature and they may be explained in terms of chemical dissolution of the anode (4), chemical attack of both anode and cathode, which can occur due to acidity and alkalinity produced in the vicinity of the electrodes (31) and pitting corrosion of the anode, caused by chloride ions (32). Figure 6 shows the amount of dissolved aluminum when an aluminum plate was dipped into a NaCl solution for 24 h. One can observe that as the chloride concentration increases, the amount of dissolved aluminum is higher, which is consistent to the literature data that says that the higher the chloride concentration, the higher is the corrosion promoted by Cl-ions over aluminum surface (33)(34)(35)(36)(37)(38)(39). It is also possible to notice that the amount of chemically dissolved aluminum is small.…”
Section: Resultssupporting
confidence: 81%
“…These super-Faradaic efficiencies are reported in the literature and they may be explained in terms of chemical dissolution of the anode (4), chemical attack of both anode and cathode, which can occur due to acidity and alkalinity produced in the vicinity of the electrodes (31) and pitting corrosion of the anode, caused by chloride ions (32). Figure 6 shows the amount of dissolved aluminum when an aluminum plate was dipped into a NaCl solution for 24 h. One can observe that as the chloride concentration increases, the amount of dissolved aluminum is higher, which is consistent to the literature data that says that the higher the chloride concentration, the higher is the corrosion promoted by Cl-ions over aluminum surface (33)(34)(35)(36)(37)(38)(39). It is also possible to notice that the amount of chemically dissolved aluminum is small.…”
Section: Resultssupporting
confidence: 81%
“…The extremely aggressive and very mobile chlorine anions [30e33] continuously attack the metallic surface, resulting in oxide layer perforation [34], followed by complete metallic dissolution [5,35].…”
Section: In Situ Chrono-potentiometric Measurementsmentioning
confidence: 99%
“…In conclusion, the degradation of the barrier layer is strongly correlated with the presence of chlorine, but the latter is neither necessary nor sufficient to promote the process. Looking at the literature68–71 confirmed that other factors may affect the stability of the aluminum oxide and thereby cause further corrosion of the aluminum: The oxide is not stable in acidic (pH < 4) or alkaline (pH > 9) environments. Aggressive fluoride ions may attack the oxide locally. Some elements (Ga, Tl, In, Sn, Pb) may become incorporated in the oxide and destabilize it. In order to develop durable products, one would need to rely on longstanding aluminum layers, both D and F systems appear to be good candidates, with a preference for the latter that does not contain chlorine. …”
Section: Resultsmentioning
confidence: 99%